Implementation Of Religious Moderation In Islamic Higher Education Institutions In The Indonesia-Malaysia Border Region - Sudianto; Syahruddin Usman; Andi Aderus; Purniadi Putra (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2025)
This research aims to analyze the forms of religious moderation practiced within the environment of the Sultan Muhammad Syafiuddin Islamic Institute of Religion in Sambas, West Kalimantan. As an Islamic higher education institution located in the Indonesia-Malaysia border region, IAIS Sambas has a unique diversity of students coming from various religious and cultural backgrounds. This research uses a descriptive qualitative approach with a case study method, where data is collected through in-depth interviews, participatory observations, and document analysis related to institutional policies and activities. The research results show that the implementation of religious moderation at IAIS Sambas is realized through various programs, such as the establishment of interfaith dialogue forums, the integration of pluralism and diversity values into the curriculum, the organization of community activities on religious holidays, and scientific research and publications that support the dissemination of the concept of religious moderation. In addition, this institution actively collaborates with local communities and religious organizations to strengthen social harmony in society. The implications of this research indicate that the approach taken by IAIS Sambas can serve as a model for other higher education institutions, especially in areas with high religious and cultural pluralism, in creating an academic environment that is tolerant, inclusive, and conducive to religious harmony. Thus, this research contributes to the strengthening of the concept of religious moderation as a tool to prevent conflict and build a harmonious society amidst diversity.